Pengaruh Lingkungan Kerja Fisik dan Motivasi Kerja terhadap Kinerja Guru di SMP Negeri 03 dan SMA Negeri 03 Kecamatan Talang Ubi Kabupaten Penukal Abab Lematang Ilir - Pratama, Roni; Hadjri, M. Ichsan; Farla, Wita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of Physical Work Environment and Work Motivation on Teacher Performance in SMP Negeri 03 and SMA Negeri 03 Talang Ubi District, Penukal Abab Lematang Ilir Regency. The population of this study were all teachers at SMP Negeri 03 and SMA Negeri 03. The sample in this study were 36 respondents totaling 56 respondents.. This type of research is Descriptive research with a Quantitative approach. The data used is primary data. Data collection methods using questionnaire techniques. Data analysis techniques are Multiple Linear Regression, F test, Determination Coefficient T test, and Correlation Coefficient test. The results of Multiple Linear Regression Variable Physical Work Environment and Work Motivation have a positive influence on Teacher Performance in SMP Negeri 03 and SMA Negeri 03 Talang Ubi District Penukal Abab Lematang Ilir Regency. The results of the F test analysis show that simultaneously there is a significant effect of Physical Work Environment Variables and Work Motivation have a significant effect on Teacher Performance in State Junior High School 03 and State Senior High School 03 Talang Ubi District Penukal Abab Lematang Ilir Regency. The partial t test results show that the Physical Work Environment and Work Motivation Variables have a significant effect on Teacher Performance in SMP Negeri 03 and SMA Negeri 03, Talang Ubi District, Penukal Abab Lematang Ilir Regency. Analysis of the Coefficient of Determination shows that 67.1% of the variables of Physical Work Environment and Work Motivation affect Teacher Performance in State Junior High School 03 and State Senior High School 03, Talang Ubi District, Penukal Abab Lematang Ilir Regency, while the remaining 32.9% is influenced by other variables not included in this study.